Studies from a Retranslation Culture The Turkish Context - Berk Albachten, Özlem; Tahir Gürçağlar, Şehnaz; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book highlights the unique history and cultural context of retranslation in Turkey, offering readers a survey of the diverse range of fields, disciplines, and genres in which retranslation has assumed a central position. Further, it addresses largely unexplored issues such as retranslation in Ottoman literature, paratextual positioning and marketing of retranslations, legal retranslation, and retranslation in music. As such, it makes a valuable contribution to the growing body of research on retranslation by placing special emphasis on non-literary translation, making the role of retranslation particularly visible in connection with politics and philosophy in Turkey. .
Chapter 1 Introduction: Mutability in Retranslation -- Chapter 2 On Gulistan's Turkish (Re)translations: A Chronological Survey through Paratextual Data -- Chapter 3 Elucidating or (Un)breaking the Chain? Intralingual Translations and Retranslations of Şeyh Galib's Hüsn ü Aşk. A. Handan Konar -- Chapter 4 Turkish Retranslations of Philosophical Concepts in Kritik der reinen Vernunft -- Chapter 5 (Re)translations of the European Convention on Human Rights in Turkish -- Chapter 6 The Turkish Retranslations of Marx's Das Kapital as a Site of Intellectual and Ideological Struggle -- Chapter 7 The Indicative Role of Retranslations for the Turkish Leftist Discourse: Using Berman's Translation Criticism Path to Analyze Manifest der Kommunistischen Partei as a Case -- Chapter 8 Up to Date as Long as Retranslated: Thomas More's Utopia in Turkish -- Chapter 9 Retranslating and Repackaging a Literary Masterpiece from a Peripheral Language: The Functions of Paratexts in Recontextualizing Literary Translations -- Chapter 10 Retranslation, Paratext, and Recontextualization: Le Comte de Monte Cristo and The Hound of Baskervilles in Turkish (Re)translations -- Chapter 11- Why "Sway" Again? Prosodic Constraints and Singability in Song (Re)translation.
Keywords: Translating and interpreting; Comparative literature; Culture -- Study and teaching; Language Translation; Comparative Literature; Cultural Studies